2016
DOI: 10.1016/j.cell.2016.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Causal Genetic Drivers of Human Disease through Systems-Level Analysis of Regulatory Networks

Abstract: Cell 159, 402-414; October 9, 2014) In the above article, we inadvertently omitted the following acknowledgment:The results published here are, in part, based upon data generated by the Therapeutically Applicable Research to Generate Effective Treatments (TARGET) initiative managed by the NCI. The data used for this analysis (phs000218.v15.p5.c1) are available at http:// www.ncbi.nlm.nih.gov/projects/gap/cgi-bin/study.cgi?study_id=phs000218.v15.p5. Information about TARGET can be found at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 0 publications
2
29
0
Order By: Relevance
“…These alterations were not statistically significant by genome wide association studies. In addition, novel alterations predicted by the methodology for the mesenchymal subtype of high-grade glioma were experimentally validated as the most frequent causal determinants of the disease subtype [40]. Critically, this analysis could be performed on an individual sample basis, thus completely avoiding mechanism heterogeneity as a confounding factor that would negatively affect discovery when averaging on patients representing distinct mechanisms (e.g., all AD-affected individuals).…”
Section: Creating the Assembly Manual Of The Alzheimer's Cellmentioning
confidence: 99%
See 2 more Smart Citations
“…These alterations were not statistically significant by genome wide association studies. In addition, novel alterations predicted by the methodology for the mesenchymal subtype of high-grade glioma were experimentally validated as the most frequent causal determinants of the disease subtype [40]. Critically, this analysis could be performed on an individual sample basis, thus completely avoiding mechanism heterogeneity as a confounding factor that would negatively affect discovery when averaging on patients representing distinct mechanisms (e.g., all AD-affected individuals).…”
Section: Creating the Assembly Manual Of The Alzheimer's Cellmentioning
confidence: 99%
“…More recently, we have shown that MARINa-inferred MRs represent tight regulatory bottlenecks that integrate a large spectrum of germline variants and somatic alterations in upstream pathways [40]. These bottlenecks allow genetic variants and alterations patterns that are substantially distinct in different patients to converge on activating or inactivating key genetic programs that represent the hallmarks of the disease.…”
Section: Creating the Assembly Manual Of The Alzheimer's Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods have shifted from intuitive inference of local connectivities to comprehensive analysis of large networks, involving heterogeneous data sets from high-throughput experiments and complex theoretical tools (6)(7)(8)(9)(10). Despite significant advances, a fundamental reverse engineering bottleneck is the ability to discriminate between direct and indirect connections.…”
mentioning
confidence: 99%
“…Recurrent epigenetic alterations, especially DNA methylation [52], and large-scale functional screens [53][54][55][56] can also be used to identified novel candidate drivers. Then, these alterations or perturbations are integrative analyzed with gene expression variations (either cis-or trans-acting effects), the functional indications of genetic alterations [57][58][59][60][61]. TCGA researchers have used this method to identify molecular subtypes of various cancers, such as the BRAF V600E -like and RAS-like subtypes of papillary thyroid carcinoma [62].…”
Section: Regulatory Integrative Clusteringmentioning
confidence: 99%